School education system in Ancient China - Khuan Tszynshen (Vasyl Stefanyk Precarpathian National University, 2017)
The article covers the school education system in the Ancient China, which waswidespread for centuries. The basic principles of education in the Ancient China and their rolein the development of the world educational thought are analyzed. Key words: education system, Ancient China, sources of educational thought, the historyof school, education and bringing-up traditions.